A cycloparaphenylene nanoring with graphenic hexabenzocoronene sidewalls. Issue 44 (13th May 2016) - Lu, Dapeng; Wu, Haotian; Dai, Yafei; Shi, Hong; Shao, Xiang; Yang, Shangfeng; Yang, Jinlong; Du, Pingwu
Abstract : A novel hexabenzocoronene-containing cycloparaphenylene carbon nanoring is rationally designed and synthesized. The cycloparaphenylene structure is firstly observed by STM and its photophysical properties were further studied. Abstract : Herein we report the synthesis of a novel hexabenzocoronene-containing cycloparaphenylene carbon nanoring, cyclo[12]-paraphenylene[2]-2, 11-hexabenzocoronenylene, by metal-mediated cross-coupling reactions. The nanoring was accomplished by rationally designed palladium-catalyzed coupling of diborylhexabenzocoronene and L-shaped cyclohexane units, followed by nickel-mediated C–Br/C–Br coupling and the aromatization of cyclohexane moieties. The structure was confirmed by NMR and HR-MS. Especially, the cycloparaphenylene structure is firstly observed by STM. The photophysical properties were studied using UV-Vis spectroscopy, photoluminescence (PL) spectroscopy, and theoretical calculations.